The Influence of Transcultural Humility Simulation Development Activities on the Cultural Competence of Baccalaureate Nursing Students - (:unkn) unknown (My University, 2016)
One way to mitigate health disparities in the provision of nursing care and impact social justice with vulnerable populations is the development of cultural competence. Although addressed in nursing curricula, gaps in how to best address cultural competence remain. A study was undertaken to determine whether participation in a researcher-designed intervention, entitled Transcultural Humility Simulation development, based on components of Campinha-Bacote’s model with an emphasis on “becoming” culturally competent, improved cultural competence in graduating baccalaureate nursing students. A longitudinal, descriptive, quasi-experimental, pretest-posttest comparison group design using embedded mixed methods was used. A total of 57 student participants from one baccalaureate nursing school in the western US were randomly assigned to the intervention group (n = 22) or the comparison group (n = 35). All participants completed the Inventory for Assessing the Process of Cultural Competence-Student Version before and after the intervention. Intervention participants also completed three written reflection exercises the day of the workshop. A subgroup of participants in the intervention group (n = 12) and the comparison group (n = 8) were interviewed two to three months after graduation. No statistically significant differences were obtained between groups while treating the pretest as a covariate. Participants who identified as more than one race on the demographic survey perceived they were more culturally competent than those who identified as one race, F ratio of F(10, 3) = 15.13, p = .02. Analysis of participant reflections during the intervention indicated they anticipated incorporating cultural competence into their practice by shattering preconceived perceptions, constructing innovative insights, improving effective communication, and emerging personal development. Once in practice, they incorporated cultural competence through cultivating nursing-person relationships, providing quality nursing care, serving the patient and family, establishing extraordinary communication and approaching care with humility. This study suggests that bringing attention to cultural competence through participation in Transcultural Humility Simulation Development could raise awareness and foster developmental growth among student participants through transformative learning, epistemic belief change, and double-loop learning.
Keywords: Campinha-bacote; Cultural Competence; Health Disparities; Mixed Methods; The Inventory for Assessing the Process of Cultural Competence-Student Version; Transcultural Humility Simulation Development